2018
DOI: 10.1055/a-0594-2404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glucose Metabolism Disorders on IGF-1 Levels in Patients with Acromegaly

Abstract: In this study, we aimed to evaluate the presence of glucose metabolism abnormalities and their impact on IGF-1 levels in patients with acromegaly. Ninety-three patients with acromegaly (n=93; 52 males/41 females) were included in this study. Patients were separated into three groups such as; normal glucose tolerance (n=23, 25%), prediabetes (n=38, 41%), and diabetes mellitus (n=32, 34%). Insulin resistance was calculated with homeostasis model assessment (HOMA). HOMA-IR > 2.5 or ≤2.5 were defined as insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Information regarding 5,010 patients (2,079 men, 2,931 women) who visited outpatient clinics (Plastic Surgery, Orthopedics, Ophthalmology, Dermatology, Family Medicine, Dentistry, Otorhinolaryngology, Allergy and Immunology) from December 2018 to July 2019 was reviewed, and excluded based on the following exclusion criteria: (1) a medical history of liver diseases, renal diseases, cancer, diabetes mellitus, cardiac disorder, pulmonary disorder, or thyroid disorder or alanine aminotransferase >54 IU/L, aspartate aminotransferase >32 IU/L, estimated glomerular filtration rate <60 mL/min/1.73 m 2 , glucose ≥126 mg/dL, or C-reactive protein >10 mg/L; (2) no test results for liver enzyme, glucose, and creatinine; (3) the use of estrogen medication; and (4) ethnicity other than Korean. We defined "healthy" subjects to be those who passed all the exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information regarding 5,010 patients (2,079 men, 2,931 women) who visited outpatient clinics (Plastic Surgery, Orthopedics, Ophthalmology, Dermatology, Family Medicine, Dentistry, Otorhinolaryngology, Allergy and Immunology) from December 2018 to July 2019 was reviewed, and excluded based on the following exclusion criteria: (1) a medical history of liver diseases, renal diseases, cancer, diabetes mellitus, cardiac disorder, pulmonary disorder, or thyroid disorder or alanine aminotransferase >54 IU/L, aspartate aminotransferase >32 IU/L, estimated glomerular filtration rate <60 mL/min/1.73 m 2 , glucose ≥126 mg/dL, or C-reactive protein >10 mg/L; (2) no test results for liver enzyme, glucose, and creatinine; (3) the use of estrogen medication; and (4) ethnicity other than Korean. We defined "healthy" subjects to be those who passed all the exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The level of insulin-like growth factor I (IGF-I) is affected by various factors such as age, sex, systemic illness, ethnicity, and the type of the analytical method [1,2]. Therefore, reference intervals of IGF-I considering those factors are necessary for the interpretation of measurement values in a given population.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin mediated increase in both IGFs occurs due to the transcript stability increasing effect of this hormone rather than an increase in gene transcription [ 84 ]. In turn, transcription of the IGF-1 gene directly may be influenced by glucose metabolism in the liver [ 3 ] and its disorders [ 85 ]. Similarly, hepatic uptake of certain AAs, induced by GH or insulin, facilitates the expression of IGF-1 by stabilizing IGF-1 mRNA [ 3 ].…”
Section: Igf System Components and Signalingmentioning
confidence: 99%
“…In another study, IGF-1% upper limit of normal (ULN)/GH ratio was used to assess the effect of glucose metabolism disorders on IGF-1 levels. A reduction in this ratio was demonstrated in patients with IR (HOMA-IR > 2.5) or prediabetes [ 85 ]. Similarly, Maione et al demonstrated a positive correlation between baseline ULN IGF-1 levels and DM II, even after adjustment for age, BMI, and both factors [ 174 ].…”
Section: Igf-1 and Colorectal Cancer Pathogenesismentioning
confidence: 99%
“…High GH and in-sulin-like growth factor-1 (IGF-1) levels affect many tissues, including muscle and fat, where they dysregulate carbohydrate, protein, and fat metabolism [3]. The accompanying insulin resistance (IR), prediabetes, diabetes mellitus (DM), hyperlipidemia, and concom-itant hypertension increase the risk of cardiovascular disease in acromegalic patients [4][5][6], in whom it is the most common cause of death [7].…”
Section: Introductionmentioning
confidence: 99%